2016
DOI: 10.1007/s12325-016-0281-1
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Patients with Ovarian Cancer for Germline BRCA Mutation Testing: Findings from Guidelines and a Systematic Literature Review

Abstract: AstraZeneca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 54 publications
1
42
1
1
Order By: Relevance
“…Several recent studies have shown that any woman with epithelial ovarian cancer is eligible by this criterion [5], [6], [7], [8], [9]. Many centers use family history of cancer to determine test eligibility, but this is much less effective in identifying women with BRCA mutations [45]. Some centers restrict testing to nonmucinous or high-grade serous ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that any woman with epithelial ovarian cancer is eligible by this criterion [5], [6], [7], [8], [9]. Many centers use family history of cancer to determine test eligibility, but this is much less effective in identifying women with BRCA mutations [45]. Some centers restrict testing to nonmucinous or high-grade serous ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The more restrictive testing guidelines used, which limited testing to those at “high risk,” as defined by a personal history of breast cancer or family history of breast and/or ovarian cancer, contributed somewhat to the under testing. Such restrictions will lead to 40% of inherited mutations being missed . However, even in the current era of more inclusive testing criteria, the majority of women are still not referred for genetic counseling/testing .…”
Section: Genetics Referral/brca Testing Rates and Barriersmentioning
confidence: 99%
“…Such restrictions will lead to 40% of inherited mutations being missed. 3,60 However, even in the current era of more inclusive testing criteria, the majority of women are still not referred for genetic counseling/ testing. 5,55,56 Additional reasons for the failure to get to the genetics team and thus not be tested include: 1) process issues with genetic counseling/testing; 2) physician lack of knowledge; 3) patient unawareness of testing; and 4) patient refusal.…”
Section: Genetics Referral/brca Testing Rates and Barriersmentioning
confidence: 99%
“…There is an inherited component to ovarian cancer; between 5.8% and 24.8% of cases can be attributed to germline mutations in BRCA1 and BRCA2 genes 2. Until recently, BRCA genetic testing has been provided by clinical genetics services.…”
Section: Introductionmentioning
confidence: 99%